Consequences of the economic crisis to consumer behaviour in Greece - an empirical analysis. (2016) - Polychronidou, Persefoni; Florou, Giannoula; Karasavvoglou, Anastasios
In this paper, the consequences of the economic crisis to consumer behaviour are studied. Results and conclusions of the conducted empirical research of a sample consisted of 1, 118 people are presented. Factors that have been studied are age, sex, economical status, the way and the frequency of consuming clothing, foot wear, cosmetics, accessories, new technologies and entertainment cost.